Two new species of Pentacalia (Compositae, Senecioneae) from northern Andes - Calvo, Joel; Buira, Antoni (Phytotaxa, 2018)
Recent collections carried out in southern Colombia (Putumayo) and southern Ecuador (Zamora-Chinchipe) lead us to describe two new species of Pentacalia based on morphological evidence. One of them displays lateral, axillary synflorescences and disciform capitula, whereas the other keys out in the group of terminal synflorescences and disciform capitula. Taxonomically useful characters are provided to easily distinguish each species from its closest relatives, as well as detailed pictures of living plants and distribution maps. Adjusted keys for the Colombian and Ecuadorian species are also presented.